PENGARUH EKSTRAK DAUN GEDI (ABELMOSCHUS MANIHOT L.) TERHADAP GAMBARAN HISTOPATOLOGI AORTA TIKUS WISTAR DENGAN DIET ATEROGENIK - Papodi, Nadya Nadiratika (Universitas Sam Ratulangi, 2014)
Abstract: High blood cholesterol is a major risk factor for atherosclerosis. Gedi plants contain polyphenolic compounds that can lowering blood cholesterol levels. This study aimed to find out the effect of gedi (Abelmoschus manihot L) leaves extract on histopatologic features of aorta of those wistar rats, which had been administered an atherogenic diet. This was an experimental study on animal using 20 Wistar rats as samples. The rats were divided into 4 different groups, 5 rats for each group. Negative control group was fed only pelet, positive control group was fed pork fat as much as 2 ml/day, group C was fed on pork fat and gedi leaf extract, and group D was fed on pork fat then continued with gedi leaf extract. The results indicated that administration of 30 mg gedi leaf extract showed a histopathologic feature which is decreasing of foam cells. Conclusion: Microscopically, aorta of those rats fed on pork lard diet showed a number of foam cells in tunica intima and media whereas the rats that were fed on pork lard along with gedi leaf extract, generally there were no foam cells, but there aresome parts which contain few foam cells. On the group of Wistar rats which were fed on pork lard, continued with gedi leaf extract showed less foam cells compared to the positive control group.Keywords: Gedi leaf extract, pork lard, foam cell.Abstrak: Kadar kolesterol darah yang tinggi merupakan faktor risiko utama terjadinya aterosklerosis. Tumbuhan gedi mengandung senyawa polifenol yang dapat menurunkan kadar kolesterol darah. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak daun gedi terhadap gambaran histopatologi aorta tikus wistar dengan diet aterogenik. Hewan uji yang digunakan berupa 20 ekor tikus Wistar yang dibagi ke dalam 4 kelompok, masing-masing kelompok terdiri dari 5 ekor tikus. Kelompok kontrol negatif hanya diberikan pelet biasa, kelompok kontrol positif diberikan diet lemak babi 2ml/hari, kelompok C diberikan diet lemak babi bersamaan dengan ekstrak daun gedi, dan kelompok D diberikan lemak babi kemudian dilanjutkan dengan pemberian ekstrak daun gedi. Hasil penelitian memperlihatkan bahwa pemberian ekstrak daun gedi 30 mg mampu memberikan gambaran histopatologi aorta berupa berkurangnya jumlah sel busa. Simpulan: Secara mikroskopik, aorta tikus wistar yang diberi lemak babi menunjukkan adanya penumpukan sel-sel busa pada tunika intima dan media, sedangkan pada aorta tikus wistar yang diberi lemak babi bersamaan dengan ekstrak daun gedi maupun yang dilanjutkan dengan ekstrak daun gedi ditemukan berkurangnya jumlah sel-sel busa.Kata Kunci : Ekstrak daun gedi, Lemak babi, Sel busa.